2015
DOI: 10.1186/s12889-015-1384-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-metabolic health risks in indigenous populations of Southeast Asia and the influence of urbanization

Abstract: BackgroundSouth East Asia (SEA) is home to over 30 tribes of indigenous population groups who are currently facing rapid socio-economic change. Epidemiological transition and increased prevalence of non-communicable diseases (NCD) has occured. In Peninsular Malaysia, the Orang Asli (OA) indigenous people comprise 0 · 6% (150,000) of the population and live in various settlements. OA comprise three distinct large tribes with smaller sub-tribes. The three large tribes include Proto-Malay (sub-tribes: Orang Selet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 10 publications
2
57
1
1
Order By: Relevance
“…We reported a high prevalence of cardio-metabolic diseases such as obesity, pre-diabetes, insulin resistance and pre-hypertension among Temiar. These non-communicable diseases were previously not reported in OA, but recent studies have indicated their high prevalence, especially in OA tribes living near cities 1,3,15 . Increased cardio-metabolic risks were also reported in aboriginal Torres Straits Islanders from Australia 16 , the Jaguapiru indigenous community in Brazil 17 and the Rang Bothiya tribe in India 18 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We reported a high prevalence of cardio-metabolic diseases such as obesity, pre-diabetes, insulin resistance and pre-hypertension among Temiar. These non-communicable diseases were previously not reported in OA, but recent studies have indicated their high prevalence, especially in OA tribes living near cities 1,3,15 . Increased cardio-metabolic risks were also reported in aboriginal Torres Straits Islanders from Australia 16 , the Jaguapiru indigenous community in Brazil 17 and the Rang Bothiya tribe in India 18 .…”
Section: Discussionmentioning
confidence: 88%
“…They are categorized into three main groups, namely Negrito, Senoi and Proto Malay. OAs are widely spread across the Peninsular and range from semi-nomadic deep forest hunter-gatherers such as the Jahai to resettled communities such as Mah Meri to urbanized city-fringe dwellers such as Orang Seletar 1 . This study focused on the Temiar who are a subtribe of Senoi and are believed to be descendants of the first Neolithic farmers who migrated to the Malay Peninsula 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While underweight and stunting are common in Orang Asli children, overweight and obesity are becoming increasingly prevalent among the adults. Studies across the sub-tribes showed that approximately 10-50% Orang Asli adults were overweight and/or obese, with women more likely to be overweight or obese than men [39][40][41][42][43]. There is also accumulating evidence of metabolic risks (i.e.…”
Section: Studies On Orang Asli Health Food and Nutrition Securitymentioning
confidence: 99%
“…There is also accumulating evidence of metabolic risks (i.e. impaired glucose intolerance, hypertension, central obesity, hyperlipidaemia) in the Orang Asli adults [41][42][43][44][45][46]. The rising prevalence of metabolic risks could lead to increasing occurrence of diabetes mellitus, hypertension and cardiovascular diseases in the indigenous community.…”
Section: Studies On Orang Asli Health Food and Nutrition Securitymentioning
confidence: 99%